Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Cornejo Arrieta, Diego Alonso (2019)
The purpose of this analysis and diagnosis is to propose a Strategic Plan of Camposol S.A., an entity whose operation focuses on the production and export of fresh fruits, vegetables and seafood to different countries of the world. The aforementioned activities are carried out in northern Peru and have a significant impact on the national economy, especially for the Agribusiness sector. That said, what is sought with this Strategic Plan, is to design a series of strategies for the Strategic Business Units of Camposol, in order to be recognized as one of the largest export companies of fresh and healthy food in the world, that go hand in hand, with the sustainability challenges they outlined. The strategies that will be proposed are focused on the vision, mission, values, principles, policies and code of ethics of Camposol, in order to establish indicators that guide them towards their goals and proposed goals for the future. After executing these strategies, Camposol will see the increase in the value of the company, a better market positioning and expansion into new markets.